Verification, Model Checking, and Abstract Interpretation 11th International Conference, VMCAI 2010, Madrid, Spain, January 17-19, 2010. Proceedings - Barthe, Gilles; Hermenegildo, Manuel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 11th International Conference on Verification, Model Checking, and Abstract Interpretation, VMCAI 2010, held in Madrid, Spain, in January 2010. The 21 papers included in this volume were carefully reviewed and selected from 57 submissions. In addition 3 invited talks and 3 invited tutorials are presented. Topics covered by VMCAI include program verification, program certification, model checking, debugging techniques, abstract interpretation, abstract domains, static analysis, type systems, deductive methods, and optimization.
Invited Talks -- Analysis of Systems with Stochastic Process Creation -- Verifying Concurrent Programs with Chalice -- Static Timing Analysis for Hard Real-Time Systems -- Invited Tutorials -- Abstract Interpretation-Based Protection -- Advances in Probabilistic Model Checking -- Building a Calculus of Data Structures -- Regular Papers -- Temporal Reasoning for Procedural Programs -- Improved Model Checking of Hierarchical Systems -- Path-Oriented Reachability Verification of a Class of Nonlinear Hybrid Automata Using Convex Programming -- Complexity Bounds for the Verification of Real-Time Software -- An Abstract Domain to Discover Interval Linear Equalities -- Interpolant Strength -- Checking Bounded Reachability in Asynchronous Systems by Symbolic Event Tracing -- Invariant and Type Inference for Matrices -- Deriving Invariants by Algorithmic Learning, Decision Procedures, and Predicate Abstraction -- Automatic Abstraction for Congruences -- Shape Analysis of Low-Level C with Overlapping Structures -- Abstract Threads -- Shape Analysis with Reference Set Relations -- Shape Analysis in the Absence of Pointers and Structure -- An Analysis of Permutations in Arrays -- Regular Linear Temporal Logic with Past -- Model-Checking In-Lined Reference Monitors -- Considerate Reasoning and the Composite Design Pattern -- RGSep Action Inference -- Best Probabilistic Transformers -- Collections, Cardinalities, and Relations.
Keywords: Computer science; Software engineering; Computer software; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Algorithm Analysis and Problem Complexity; Programming Techniques; Software Engineering/Programming and Operating Systems